2019
DOI: 10.3390/cells8030226
|View full text |Cite
|
Sign up to set email alerts
|

Excessive Reactive Iron Impairs Hematopoiesis by Affecting Both Immature Hematopoietic Cells and Stromal Cells

Abstract: Iron overload is the accumulation of excess iron in the body that may occur as a result of various genetic disorders or as a consequence of repeated blood transfusions. The surplus iron is then stored in the liver, pancreas, heart and other organs, which may lead to chronic liver disease or cirrhosis, diabetes and heart disease, respectively. In addition, excessive iron may impair hematopoiesis, although the mechanisms of this deleterious effect is not entirely known. In this study, we found that ferrous ammon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 55 publications
0
19
0
Order By: Relevance
“…Oxidative stress is an important contributor to diabetic complications and exacerbates cellular damages. Excessive production of ROS contributes to the initiation of programmed cell death in diabetes, which increased neuronal apoptosis in diabetes [ 44 , 45 ]. In view of the important role of oxidative stress, strategies for intervention of ROS-induced cell apoptosis may be of particular relevance.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress is an important contributor to diabetic complications and exacerbates cellular damages. Excessive production of ROS contributes to the initiation of programmed cell death in diabetes, which increased neuronal apoptosis in diabetes [ 44 , 45 ]. In view of the important role of oxidative stress, strategies for intervention of ROS-induced cell apoptosis may be of particular relevance.…”
Section: Discussionmentioning
confidence: 99%
“…Excessive iron accumulation in the body can cause liver damage, cardiovascular damage, neurodegenerative diseases and many aging‐related diseases [21]. Iron overload has a profound effect on immature hematopoietic cells and stromal cells, and thereby destroys the hematopoietic process [22]. Previous studies have indicated that iron homeostasis is crucial for various kinds of stem cell.…”
Section: Discussionmentioning
confidence: 99%
“…An in vitro study examined the effects of iron load (that may simulate the process of iron infusion in patients with IDA) on the function of primary hematopoietic cells and stromal cell lines and found that iron overload impairs normal hematopoietic cells and modifies the function of stromal cells, indicating that iron overload impairs the whole hematopoietic system. The authors suggested that the deleterious effects of iron were mediated through its impact on hematopoietic stem/progenitor cells as well as in differentiated hematopoietic via reactive oxygen species (ROS) accumulation [24]. In addition, an in-vitro study showed that ferrous ammonium sulfate (FeAS) induced growth arrest and apoptosis in immature hematopoietic cells and led to insulin-like growth factor binding protein 2 (IGFBP2) and insulin-like growth factor 1 (IGF-1) down-regulation.…”
Section: Discussionmentioning
confidence: 99%